Implementasi Perubahan Biodata (Status Perkawinan) pada Website Klampid New Generation (KNG) dalam Upaya Tertib Administrasi Kependudukan di Kecamatan Pakal Kota Surabaya - Purwanto, Regina Maulidya Putri; Nafi’ah, Binti Azizatun (VISA: Journal of Vision and Ideas, 2024)
Before 2017, family cards only listed marital status as “married”, “not married”, “divorced”, and “divorced”. This causes legal impacts for husbands, wives and children. The Population and Civil Registration Service of the City of Surabaya is promoting a program to change biodata (marital status) on family cards, which in its implementation is assisted by lower agencies, such as sub-districts, sub-districts, Great Surabaya Cadres (KSH), RW heads and RT heads. The method used in this writing is descriptive qualitative. The results of this research refer to the implementation of changes in biodata (marital status) recorded in efforts to orderly population administration in the Surabaya City area with indicators according to Ripley and Franklin (1986) which include compliance, smooth implementation of routines and functions and the realization of the desired performance. The research results show that the biodata change program policy (marital status) is able to increase public awareness of the importance of managing population administration and has fulfilled and implemented three variables from the policy implementation theory of Ripley and Franklin (1986).